CENTRAL BANK INDEPENDENCE AND POLICY OUTCOMES: A TRANS-BOUNDARY COMPARISON - Iksan, Muhamad; Konishi, Tetsu (Bank Indonesia, 2022)
This paper examines how Central Bank Independence (CB Independence), using a dataset that compiled by Garriga (2016), can explain the policy outcomes. This dataset was mainly compiled from Cukierman’s work (1995). The dataset identifies statutory reforms affecting CB Independence, their direction, and the attributes necessary with the aim of building on previous literature, the most widely used Cukierman, Webb and Neyapti index. The focus of this paper is empirically estimating causal inferences of inflation and economic growth with an explanatory variable of the central bank Independence measures. It has four components including central bank CEOs, central bank objectives, policy formulations and central bank lending limit policies. The second focus of this paper aims to harness the Asia Financial Crisis 1998-1999, as natural experiment to understand effect of crises by using semi-experimental method Difference-In-Difference (DID). Panel data regression and DID are two empirical research methods applied in this research. This paper proposes all four CB Independence measures can explain the inflation; but this paper does not find statistical support for the economic growth. Supported by DID estimation, this paper also estimates the effect of CB Independence to inflation and economic growth for the sample countries before and after the 1998 Asia financial crisis experienced by sample countries. To enrich our historicalinstitutional narrative, this paper underlines narrative under the tale of two countries – Japan and Indonesia as exemplify.